Eyes and spies : how you're tracked and why you should know - Kyi, Tanya Lloyd, 1973- (Annick Press, 2017)
"This book looks at the way information and data is collected and used by individuals, governments, companies, and organizations. Arguments for both increased security and increased privacy are offered, encouraging readers to think critically about the issues. Topics relevant to children are included, such as being tracked at school, cyberbullying, and online safety."--